2021
DOI: 10.1371/journal.pone.0247559
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of adipogenesis- and lipid metabolism-related gene expression levels in muscle, adipose tissue and liver from Wagyu-cross and Holstein steers

Abstract: The intramuscular fat (IMF) content and fatty acid composition are important meat quality traits that are mostly affected by the cattle breed. Muscle, adipose tissue and liver are important organs involved in the development of intramuscular adipose tissue. Thus, we hypothesized that there were marked differences in the adipogenesis and lipid metabolism of these tissues between Wagyu-cross and Holstein steers during the finishing phases. To test this hypothesis, we analyzed the expression levels of adipogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Studies have shown that fat deposition in backfat is related to body fat percentage, carcass cross-sectional fat area ratio, intramuscular fat, and flavor and juiciness of beef ( 5 , 6 ). In Japanese Wagyu cattle, IMF content in the longest dorsal muscle was found to be positively correlated with the percentage of subcutaneous fat and maturity in vivo ( 7 , 8 ). Therefore, the identification of key genes related to subcutaneous adipose tissue by a new method is an important strategy for carcass and meat quality genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that fat deposition in backfat is related to body fat percentage, carcass cross-sectional fat area ratio, intramuscular fat, and flavor and juiciness of beef ( 5 , 6 ). In Japanese Wagyu cattle, IMF content in the longest dorsal muscle was found to be positively correlated with the percentage of subcutaneous fat and maturity in vivo ( 7 , 8 ). Therefore, the identification of key genes related to subcutaneous adipose tissue by a new method is an important strategy for carcass and meat quality genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Since buffalo is abundant in China, it would be desirable to increase its IMF content. It is known that the IMF correlates with maturity ( 43 ) and percentage ( 44 ) of back subcutaneous fat, which therefore may be used as IMF indicator. Therefore, determining the related factors affecting subcutaneous fat deposition can provide theoretical basis for improving meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…In the biological process analysis, we identified that these miRNAs were highly enriched with genes in the TGF-β pathway, suggesting that they are plausible candidates. Recently, has been reported that TGF-β through Smad3 transcriptional repression leads to the inhibition of myogenesis differentiation [ 41 , 42 ]. Myogenic differentiation and function may need several cellular signal and growth factors, but also an appropriate environment that may be impair by statins.…”
Section: Discussionmentioning
confidence: 99%